2018
DOI: 10.3126/bjhs.v3i1.19759
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Acute Coronary Syndrome In Young People: A Hospital Based Observational Study in Western Nepal

Abstract: Introduction: Acute coronary syndrome is associated with high mortality and morbidity. The incidence of acute coronary events in young is increasing.Objectives: This study aimed at evaluating the profile of acute coronary syndrome in young people in the western part of Nepal.Methodology: A retrospective study was designed. All patients admitted for acute coronary syndromes were taken and data of acute coronary syndrome involving patients aged less than 45 years from April 2015 through December 2017 were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Smoking was seen as commonest risk factor out of the other conventional risk factors in other studies too. [14][15][16]21 This was followed by hypertension (52%), Dyslipidemia (50%), Diabetes (18%) and Obesity ( and India 22 showed 55 % and 48 % respectively which is similar to our study. We had patients with higher dyslipidemics than other studies like INTERHEART South Asian Cohort 20 and a study form Bangladesh.…”
Section: Procedures Cag Pci (N=588) Totalsupporting
confidence: 88%
See 2 more Smart Citations
“…Smoking was seen as commonest risk factor out of the other conventional risk factors in other studies too. [14][15][16]21 This was followed by hypertension (52%), Dyslipidemia (50%), Diabetes (18%) and Obesity ( and India 22 showed 55 % and 48 % respectively which is similar to our study. We had patients with higher dyslipidemics than other studies like INTERHEART South Asian Cohort 20 and a study form Bangladesh.…”
Section: Procedures Cag Pci (N=588) Totalsupporting
confidence: 88%
“…The patients with young ACS comprises from 8-13% around the globe including Nepal. [10][11][12][13][14][15][16] The most common risk factor in patients with ACS was smoking (71%). Smoking was seen as commonest risk factor out of the other conventional risk factors in other studies too.…”
Section: Procedures Cag Pci (N=588) Totalmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to a few other studies even in patients with young acute coronary syndromes where smoking was found to be the major risk factor along with hypertension, diabetes, and dyslipidemia. [16][17][18][19] There was a significant association between smoking (OR: 11.5, p:0.005), hypertension (OR:8.5, p: 0.002), and diabetes (OR: 10, p: 0.001). Similar results are seen in other studies too and there are studies where smoking and diabetes are commonly associated with multivessel diseases.…”
Section: Resultsmentioning
confidence: 99%
“…were hypertensive with 14 % diabetic and diabetes was associated with multivessel disease and poor prognosis [26].…”
Section: Discussionmentioning
confidence: 99%